The Jubilee Calendar - Mayshar, Joram (Vetus Testamentum, 2021)
I propose that the jubilee legislation intended to provide an alternative calendar system to replace the prevailing one, based on the year of the reigning monarch. In that alternative calendar, the Day of Atonement on which the jubilee was declared was to serve as the substitute for the date of the king’s accession to the throne. This proposal provides a new interpretation of Lev 25:20–22 and resolves multiple difficulties on the alignment of the sabbatical and jubilee year-counts. It implies that the jubilee cycle was intended to be forty-nine years long, with coincidence of the jubilee fallow and that of the seventh sabbatical year.